2016
DOI: 10.1177/1060826516658765
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Gender Segregation in Pre-Primary and Primary Education in Cyprus

Abstract: Although great emphasis is given on the quality of early childhood education, the demographics of the teaching personnel attract limited attention even though those characteristics are linked to the quality of education. The present study aims at exploring gender segregation in pre-primary and primary education in Cyprus, using the statistical lenses through which feminization can be understood. The article presents the number of male and female undergraduate students enrolled in preprimary and primary educati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Julian's findings included men being discouraged because of inadequate compensation, low respect and prestige, and societal norms regarding gender appropriate careers. These findings are echoed in male primary teacher research (e.g., Foster & Newman, 2005, Moss-Racusin & Johnson, 2016Rentzou, 2016) that has been conducted without using SCCT. Despite the entry of some men and women into non-traditional occupations, societal stereotyping continues to divide work along gender lines.…”
Section: Gender Non-traditional Professionsmentioning
confidence: 89%
See 2 more Smart Citations
“…Julian's findings included men being discouraged because of inadequate compensation, low respect and prestige, and societal norms regarding gender appropriate careers. These findings are echoed in male primary teacher research (e.g., Foster & Newman, 2005, Moss-Racusin & Johnson, 2016Rentzou, 2016) that has been conducted without using SCCT. Despite the entry of some men and women into non-traditional occupations, societal stereotyping continues to divide work along gender lines.…”
Section: Gender Non-traditional Professionsmentioning
confidence: 89%
“…The low salary and status of primary teaching within society could be an influential contributor to the low number of men in the profession (Rentzou, 2016). Teachers' pay in Australia is dependent on qualifications and experiences rather than gender, yet it might be more of an issue for men because of the societal view that they should be their family's principal source of income (Johnson, 2008).…”
Section: Societal Perceptions Of Male Primary Teachersmentioning
confidence: 99%
See 1 more Smart Citation
“…With few male ECE teachers in primary schools, how can we establish strategies to recruit more of them? Public recognition of outstanding male ECE teachers in primary schools and male lecturers in ECE undergraduate degrees should attract males into ECE primary schools (Rentzou, 2017;Skeleton, 2009;Svodziwa & Raymond, 2016). Research by Jones (2009) has also shown that advertising focusing on male involvement in ECE promotes the profession and reduces stereotyping.…”
Section: Introductionmentioning
confidence: 99%
“…A partnership between higher education institutions and ECE has been highlighted as a critical strategy to better prepare teachers for urban and rural ECE settings (Imazeki & Goe, 2009). Rentzou (2017) suggests that policies should be implemented to recruit males to ECE settings and sustain and support them during their HEIs studies. Society must change its stereotypical perception of attracting females to teach young learners, which may encourage men to ECE so young learners can benefit from having male and female teachers (Louw & Tshelane, 2022).…”
Section: Introductionmentioning
confidence: 99%